Classification of Medicaid Coverage on Birth Records in Wisconsin, 2011-2012. (September 2019) - Mallinson, David C.; Ehrenthal, Deborah B.
Objectives: In 2011, Wisconsin introduced the 2003 Revision of the US Standard Certificate of Live Birth, which includes a variable for principal payer. This variable could help in estimating Medicaid coverage for delivery services, but its accuracy in most states is not known. Our objective was to validate Medicaid payer classification on Wisconsin birth records. Methods: We linked 128 141 Wisconsin birth records (2011-2012 calendar years) to 54 600 Medicaid claims. Using claims as the gold standard, we measured the payer variable's validity (sensitivity, specificity, positive predictive value [PPV], negative predictive value [NPV]) overall and by maternal age, race/ethnicity, education, facility delivery volume, and the Medicaid proportion of facility delivery volume. Multivariable log-binomial regression tested the association between each characteristic and payer misclassification among Medicaid-paid births. Results: Of 128 141 birth records, 50 652 (39.5%) indicated Medicaid as the principal payer and 54 600 (42.6%) linked to a Medicaid claim. The birth record misclassified 10 007 of 54 600 (18.3%) Medicaid-paid births as non-Medicaid and 6059 of 73 541 (8.2%) non-Medicaid births as Medicaid-paid. The payer variable was less sensitive (81.7%) than specific (91.8%), and PPV and NPV were similar (∼88%). Sensitivity was highest among mothers who were Hispanic, had no high school diploma, or delivered in Medicaid-majority delivery facilities. Maternal age ≥40, maternal education >high school, and delivering in a non–Medicaid-majority delivery facility were positively associated with payer misclassification among Medicaid-paid births. Conclusion: Differential misclassification of principal payer in the birth record may bias risk surveillance of Medicaid deliveries.